DNA damage in red blood cells of dab (Limanda limanda) and haddock (Melanogrammus aeglefinus) as a marker for chemical exposure in the North-East Atlantic - Skei, Bjørn Borge (2010)
The aim of the current study was to quantify DNA damage in red blood cells from natural populations of dab (Limanda limanda) and haddock (Melanogrammus aeglefinus) in relation to chemical exposure in their natural habitat. The North-East Atlantic is a highly productive area, which also receives significant amounts of chemicals from landbased, atmospheric and offshore sources. There is reason for concern if hazardous substances in the North-East Atlantic ecosystems affect marine organisms, and a comprehensive set of biomarkers is of fundamental value in developing an integrated monitoring and assessment framework on the health status of marine ecosystems. As part of the international ICON project, dab and haddock were collected, sampled and analyzed for DNA damage in red blood cells, using the Comet assay. The lack of satisfactory storage methods have until now made the Comet assay less available in field monitoring. An objective was therefore to establish a method for the preservation of blood samples prior to Comet analysis. Another objective was to identify specific DNA lesions caused by oxidative stress. Dab and haddock were collected and sampled from designated coastal and offshore locations in the North-East Atlantic during cruises from August to late December 2008. Two stations around Iceland were used as reference stations. DNA from fish blood was stored with gradual freezing to -80°C, and direct immersion and storage in lysis buffer for up to 5 weeks. DNA damage was analyzed, using the Comet assay. The lowest background DNA damage was observed with direct immersion and storage of samples in lysis buffer. Results from the Comet assay clearly indicated that dab from coastal polluted areas (Firth of Forth) and offshore areas with nearby oil and gas activity (Ekofisk) had more DNA damage than dab from less polluted (Iceland) or offshore areas without nearby activity (Dogger Bank). The results were less clear for haddock. It was not possible to identify specific DNA lesions caused by oxidative stress based on ...